2008
DOI: 10.1016/j.pain.2008.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Course and prognostic factors of whiplash: A systematic review and meta-analysis ☆

Abstract: We conducted a systematic review and meta-analysis of prospective cohort studies of subjects with acute whiplash injuries. The aim was to describe the course of recovery, pain and disability symptoms and also to assess the influence of different prognostic factors on outcome. Studies were selected for inclusion if they enrolled subjects with neck pain within six weeks of a car accident and measured pain and/or disability outcomes. Studies were located via a sensitive search of electronic databases; Medline, Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
260
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 284 publications
(287 citation statements)
references
References 72 publications
16
260
1
4
Order By: Relevance
“…These results are consistent with the findings of Kamper et al who reported in their meta-analysis review that most of the pain recovery following whiplash occurs during the first 3 months post injury [25]. However, our results are at variance with others, who report that severe whiplash associated with neurological sequellae (WAD III) is persistent and debilitating.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the findings of Kamper et al who reported in their meta-analysis review that most of the pain recovery following whiplash occurs during the first 3 months post injury [25]. However, our results are at variance with others, who report that severe whiplash associated with neurological sequellae (WAD III) is persistent and debilitating.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, this is the first longitudinal study on agerelated changes in the posterior extensor muscles of the cervical spine in healthy individuals. Recently, more attention has been focused on the posterior extensor muscles of the cervical spine with regard to minimally invasive cervical spinal surgery [19, 29-31, 33, 34] and patients with cervical spinal trauma, such as whiplash injury [7,9,14,18]. The age-related changes in the posterior extensor muscles described in this study can serve as a control for the assessment of changes in the posterior extensor muscles associated with various cervical spinal disorders and with non-surgical and surgical treatments for these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, 94% of the chronic WAD group reported that the trauma occurred at least 2 years ago. A systematic review and meta-analysis of prospective cohort studies of subjects with acute whiplash injuries found that pain, disability, and recovery stabilize within the first 3 months after the trauma [25].…”
Section: Discussionmentioning
confidence: 99%